Hand hygiene knowledge among nurses and nursing students–a descriptive cross-sectional comparative survey using the WHO's “Hand Hygiene Knowledge Questionnaire” - Per-Ola Blomgren; Christine Leo Swenne; Birgitta Lytsy; Katarina Hjelm (Infection Prevention in Practice, 2024)
Summary: Aim: To determine the level of knowledge and explore the difference of hand hygiene between nursing students and nurses. Background: Annually, 3.8 million people in Europe acquire healthcare-associated infections, highlighting the importance of hand hygiene. Despite WHO's emphasis on the fact that greater hand hygiene knowledge correlates with improved hand hygiene compliance, several studies have shown knowledge gaps among nurses and nursing students regarding hand hygiene. Design: Descriptive cross-sectional comparative survey. Methods: A version of the WHO “Hand Hygiene Knowledge Questionnaire”, translated into Swedish, was used for data collection among nursing students in the first and last semester, and registered nurses from a university and associated hospital. Data were analyzed by descriptive statistics, and comparison between groups with Fisher's exact test, one-way ANOVA, and post-hoc tests (Pairwise Z-Tests, Tukey HSD). Results: The survey, conducted between December 2020 and January 2021, received responses from 201 participants, including 71 first semester students, 46 last semester students and 84 registered nurses, showing moderate (55.7% [50–74% correct answers]) to good (43.8% [75–100% correct answers]) knowledge levels. First-semester students scored lower (17.0 ± 2.1) than last-semester students (18.8 ± 1.8) and registered nurses (18.3 ± 2.1) out of 25 questions. Discussion: It is necessary for all groups to receive proper education on hand hygiene knowledge and to have an educational program that does not separate the groups but combines them with continuing education, since the students will someday be influencing future hand hygiene knowledge as a peer, together with the nurse.